DEGENERASI PETANI MUDA DI DESA BOCOR KECAMATAN BULUSPESANTREN KABUPATEN KEBUMEN - Daffa, Adilah Fajrin; Meiji, Nanda Harda Pratama; Apriadi, Deny Wahyu (Universitas Tanjungpura, 2022)
Farming is one of the jobs that used to be the main job for the people of Indonesia, especially people who live in villages, but this time the existence of farmers has decreased with the times. Villagers, especially youths, prefer to migrate to work in cities to get jobs that have a better income than working as farmers. This study aims to determine: (1) why the younger generation in Bocor Village does not choose to become farmers as a profession and (2) how migration is an alternative way for young people in Bocor Village to advance their careers. In this study, the method used is qualitative with a phenomenological approach. The results obtained from this study are that young people in the village want a better economic change than their families, so they hope that migrating can improve the economics of their families, compared to farmers whose income only depends on uncertain harvests. Migrating is also an option because, for young people who have just graduated from school, it is complicated to find a job because of the condition of the village that there are very few jobs and the Regency Minimum Wage (UMK) in the town is very small